2009
DOI: 10.1007/s11743-009-1116-8
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Surfactants Synthesised from Replenishable Phenolic Lipids

Abstract: The oligomers (m = 1,2,3,4 and 5) in the profile of compounds obtained in the ethoxylation of saturated cardanol with ethylene oxide have been synthesised. The first member which occurs only in traces in the reaction has now been synthesised by an improved method. This monoethoxylate of 3-pentadecylphenol and a diethoxylate of 5-pentadecylresorcinol (2-hydroxyethyl derivatives) have been synthesised by the base-catalysed reaction with ethylene carbonate. Cardanol and cardol separated from technical cashew nut-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…[146][147][148] It has been demonstrated that CNSL and saturated CNSL upon reaction with ethylene sulfate give sulfo derivatives which possess excellent surfactant properties. 149 The use of ethylene sulfate with the phenoxide is an improvement which avoids both the reaction with sulfuric acid and the need for an initial hydroxyethylation step. In recent years, several amphiphilic molecules based on cardanol have been investigated and found to be potentially useful for many industrial applications (Fig.…”
Section: Surfactantsmentioning
confidence: 99%
“…[146][147][148] It has been demonstrated that CNSL and saturated CNSL upon reaction with ethylene sulfate give sulfo derivatives which possess excellent surfactant properties. 149 The use of ethylene sulfate with the phenoxide is an improvement which avoids both the reaction with sulfuric acid and the need for an initial hydroxyethylation step. In recent years, several amphiphilic molecules based on cardanol have been investigated and found to be potentially useful for many industrial applications (Fig.…”
Section: Surfactantsmentioning
confidence: 99%
“…[83][84][85] It is reported that saturated cardanol is readily sulfonated with excess sulfuric acid in halogenated solvents at ambient temperature (Figure 2, S3-S4). [86][87][88][102][103][104] It has been demonstrated that CNSL and saturated CNSL upon reaction with ethylene sulfate gave sulfo derivatives which possess excellent surfactant properties. [89] The use of ethylene sulfate with the phenoxide is an improvement which avoids both the reaction with sulfuric acid and the need for an initial hydroxyethylation step.…”
Section: Surfactantsmentioning
confidence: 99%
“…The chemical structure of the cardanol is shown in Scheme 1, which is extensively used in the development of stabilizers (Kirschweng et al , 2017), plasticizers (Chen et al , 2016) and laminates and for insulation purposes (Balgude and Sabnis, 2014). This compound can undergo various electrophilic substitution reactions like other phenolic compounds including halogenation (Attanasi et al , 2006; Voirin et al , 2014), sulfonation (Bruce et al , 2009) and nitration (Lubi and Thachil, 2000) and also the other reactions of the hydroxyl functional group alike epoxidation and esterification (Chen et al , 2015; Thenmozhi and Murugavel, 2019). Furthermore, the use of naphthalene derivatives as a diazotization or coupling compounds is known for decades which covers the huge number of industrially important azo dyes (Mohammadi and Ghafoori, 2015; “Naphthalene Derivatives”, 2006; Rasheed, 2011).…”
Section: Introductionmentioning
confidence: 99%